2021
DOI: 10.5334/irsp.433
|View full text |Cite
|
Sign up to set email alerts
|

Positive Intergroup Interdependence, Prejudice, Outgroup Stereotype and Helping Behaviors: The Role of Group-Based Gratitude

Abstract: The present paper investigates a positive, other-oriented moral emotion: group-based gratitude, in reaction to intergroup positive interdependence or outgroup contributions to ingroup's goals. Three studies support the notion that group-based gratitude plays a role in improving intergroup attitudes between natives and immigrants in the French context. In Study 1, positive intergroup interdependence was associated with group-based gratitude, which in turn was negatively associated with prejudicial attitudes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Positive experiences involving outgroup members can aid the development of a sense of other relatedness [14], other connectedness [15], and gratitude [16], which subsequently improves outgroup perceptions. Game-based interactive storytelling provides opportunities for these various meaning-making mechanisms to take place, as the narrative is supplemented by concrete gameplay that puts players in a position to be an active participant in the story [5].…”
Section: The Link Between Meaningfulness and Positive Outgroup Attitudesmentioning
confidence: 99%
“…Positive experiences involving outgroup members can aid the development of a sense of other relatedness [14], other connectedness [15], and gratitude [16], which subsequently improves outgroup perceptions. Game-based interactive storytelling provides opportunities for these various meaning-making mechanisms to take place, as the narrative is supplemented by concrete gameplay that puts players in a position to be an active participant in the story [5].…”
Section: The Link Between Meaningfulness and Positive Outgroup Attitudesmentioning
confidence: 99%
“…Positive Intergroup Relationship. This refers to the positive interactions between individuals in different social groups and interactions taking place between the groups collectively (Rambaud et al, 2021). It is manifested through mutual respect between TL and 2LL group (ST3 and ST5) and willingness of the indigenous learner to establish connection with the target language group (ST4 and ST6).…”
Section: Exposure To Tl Materialsmentioning
confidence: 99%
“…Moreover, it may even induce feelings of gratitude. For example, a study by Rambaud, Collange, Tavani, and Zenasni (2021) has shown that immigrants who emphasized the role of their community as a positive agent by highlighting how they have contributed to the development of the host country's economy induced feelings of gratitude among the majority group members. Finally, being perceived as a positive contributor may increase perceived intergroup similarity (Dovidio, Gaertner, & Saguy, 2008), which can facilitate categorization in a common ingroup identity that includes majority and minority groups, thus reducing intergroup biases from majority group members towards the minority (Dovidio et al, 1997).…”
Section: Introductionmentioning
confidence: 99%